Endoscopic Snare Excision of Adenoma of the Papilla of Vater without Prophylactic Pancreatic-Duct Stent - Attaallah, Wafi; Gunal, Omer; Mokhtare, Sina; Ozmen, Tolga; Cingi, Asim (JOP. Journal of the Pancreas, 2014)
<!–[if gte mso 9]> Normal 0 21 false false false TR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Context The endoscopic excision of adenomas of the papilla of Vater has gained increased popularity in the recent years. Temporary pancreatic drainage has been advised to accompany snare papillectomy in order to prevent ductal obstruction and serious pancreatitis. Objectives We evaluated treatment outcome of patients who had undergone endoscopic papillectomy without pancreatic drainage. Methods Three consecutive adult patients with adenomas of the papilla of Vater presented with jaundice and pain were treated by endoscopic snare excision between October 2013 and February 2014 in a single center. ERCP procedures revealed papillary tumors and endoscopic biopsy specimens revealed tubular adenoma the papilla of Vater. Adenomas were treated by snare papillectomy method and a biliary stent was inserted as a prophylactic procedure immediately after excision of the adenoma in each case. In addition to physical examination, laboratory tests were repeated in the follow-up period after papillectomy in order to document if there is any complication particularly pancreatitis. Results None of the patients experienced an immediate complication, including pancreatitis after papillectomy. Also neither patient experienced abnormal fluctuations of laboratory tests during the follow-up. Histopathologic evaluation of the resection specimens revealed a tubular adenoma with low grade dysplasia in the first two patients and a tubular adenoma with high-grade dysplasia in the third one. Endoscopy and pathologic evaluation revealed no recurrent/residual disease during the follow-up period of these patients. Conclusion Endoscopic snare resection of adenoma of the major papilla of the duodenum is a safe and minimal invasive alternative to surgical therapy. Biliary stent is sufficient to prevent biliary ductal patency and pancreatic stenting might not be necessary to prevent pancreatitis. Image: Stent removal after 3 months of follow-up. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>